A wideband frequency agile fork‐shaped microstrip patch antenna with nearly invariant radiation patterns. Issue 7 (2nd May 2016) - Meng, Fanji; Sharma, Satish K.; Babakhani, Behrouz
ABSTRACT: A wideband frequency agile fork‐shaped microstrip patch antenna is presented. Its operating frequency is tuned by incorporating four varactor diodes, which are placed symmetrically on the patch. The operating mechanism of this antenna is also briefly discussed. The full wave analysis simulated results show that the operating frequency can be tuned from 1.47GHz to 1.84GHz (frequency agility of 26.50%) with nearly invariant radiation patterns while achieving acceptable gain throughout the operating frequency range. Finally, the proposed fork‐shaped antenna was fabricated and measured for its impedance matching and gain radiation patterns. Measurement results show reasonable agreement with the simulated data. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:623–632, 2016.